2019
DOI: 10.1177/0022429418819165
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analytic Evidence of the Criterion Validity of Gordon’s Music Aptitude Tests in Published Music Education Research

Abstract: This meta-analytic study examined the validity of Gordon’s music aptitude tests as predictors of other musical variables. The four tests analyzed were the Music Aptitude Profile (1965), Primary Measures of Music Audiation (1979), Intermediate Measures of Music Audiation (1982), and Advanced Measures of Music Audiation (1989). Separate analyses were performed for tonal, rhythm, and composite constructs of music aptitude. From 47 music education journal articles that met requirements for inclusion, 215 independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 46 publications
0
12
1
Order By: Relevance
“…Furthermore, audiation has previously been correlated with other musical outcomes (Hanson, 2019). However, in contrast to other studies where early musical training (<7 years) was shown to have a positive effect on a rhythm synchronization task (Bailey and Penhune, 2012) or on auditory-evoked responses (between 7 and 13 years) (Putkinen et al, 2014), we did not find a significant effect of musical experience on sustained attention, cognitive flexibility or audiation.…”
Section: Context and Musical Experience Influencecontrasting
confidence: 99%
“…Furthermore, audiation has previously been correlated with other musical outcomes (Hanson, 2019). However, in contrast to other studies where early musical training (<7 years) was shown to have a positive effect on a rhythm synchronization task (Bailey and Penhune, 2012) or on auditory-evoked responses (between 7 and 13 years) (Putkinen et al, 2014), we did not find a significant effect of musical experience on sustained attention, cognitive flexibility or audiation.…”
Section: Context and Musical Experience Influencecontrasting
confidence: 99%
“…In each part of the AMMA, a maximum of 40 points could be achieved. The AMMA was externally validated by comparing performance to the Musical Aptitude Profile (MAP) developed by the same author (Hanson, 2019). Correlations of the different scales ranged from r = 0.7 – 0.8.…”
Section: Methodsmentioning
confidence: 99%
“…As a result of this database search, we found that in the Chinese research literature, the most widely used test batteries are those developed by Edwin Gordon (Gordon, 1986), namely, the Primary Measures of Music Audiation (PMMA) or the Intermediate Measures of Music Audiation (IMMA), which are designed for use with different age groups. However, the validity of Gordon’s measures of music audiation has been questioned in recent studies (Gembris, 1997; Mota, 1997; Oreck, Owen, & Baum, 2003; Platz et al, 2015), and their correlations with other criterion variables tend to be weak ( r < .20, Rutkowski, 1996; r = .45–.53, Hanson, 2019). In addition, several aptitude tests have been developed for the identification of musically gifted and talented children or for supporting pupils to make decisions regarding their career development (Chen, 2003; Chen, Lin, Hsu, & Yen, 2007; Lu, Chen, & Chen, 1981).…”
Section: Introductionmentioning
confidence: 99%